Categorising and clustering knowledge in fuzzy cognitive maps. (3rd October 2019) - Metzger, Alexander E.; Gray, Steven; Douglas, Ellen; Kirshen, Paul; Haigh, Nardia
The literature on managing environmental hazards in complex human-natural systems increasingly acknowledges the importance of integrating diverse stakeholder mental models into decision-making. Participatory Fuzzy Cognitive Mapping (FCM) provides an effective tool in this process, as it allows representation of mental models as complex causal networks that aid in the study of knowledge and understandings. While most participatory FCM research has studied mental model variation using graph theory and other structural metrics, our goal is to demonstrate a generalisable approach for analysing perspectives and content. We use a novel method of knowledge categorisation to identify variation among stakeholder mental models and explore its implications for social learning and collaboration. In our case study of flood managers in Boston, Massachusetts, our findings include identification of knowledge gaps, differing priorities among individuals and across jurisdictional scales and opportunities for learning and collaboration.